At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Expand and simplify 2(5x - 1) – (2x - 5) ​

Sagot :

Answer:

2(5x - 1) – (2x - 5)

=2(5x−1)−2x+5

=10x−2−2x+5

=(10x−2x)+(−2+5)

=8x+3

Step-by-step explanation: